Anatomy, Physiology and Anthropology of Language (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
The anatomical and functional data of the structures that facilitate the production of voice, speech and language are presented, emphasizing the specific activity of the cranial nerves and the areas of the cerebral cortex involved. We refer to sound communication in animals, clarifying that it is a rudimentary function, it only provides them with basic information for their own survival. The conformation of the skull of an Australopithecus, Lucy, is considered an important anthropological fact; her minimal cranial capacity and the crude conformation of his face indicate little training for the production of advanced oral language. Her skull shape reveals little intellectual development and an elementary use of sound communication. Anthropology and evolution allow us to understand the simultaneous progression of intelligence and language. We also comment the effect called Flynn effect and its inversion, with this, we return to relating intelligence and language.
Keywords: voice, word, language, evolution, cognition, intelligence